PERANAN NATAH DI DALAM KEHIDUPAN MASYARAKAT BALI - Suarya, I Made (Jurnal Natah; Vol. 1, No. 1 Februari 2003, 2012)
At first glance natah seems equal to a house yard. Yet, if we trace deeply that natah has the unique concept that is completely diverse with house yard. Its uniqueness can be not released from the distinctiveness of Balinese community life thus natah has the significant role in Balinese community life. Natah has some important roles in Balinese community life. First of all, natah has a certain place hence it has not just meaning as a space but also as a place. Second, natah is as orientation of buildings surrounding. Third, natah has a certain dimension that is taken from the body measurement of the household head or the Hindu Priest by doubling it be based on a certain sloka as index of provider character. Fourth, natah has the use as profane area and also as sacred area that is as place of the religious ritual. Fifth, natah has three meanings i.e. the meaning of emptiness, the meaning of harmony between micro cosmos and macro cosmos and the meaning of companionship between purusa and pradana.
Keywords: location arrangement, orientation, dimension, use, meaning.